2021
DOI: 10.1073/pnas.2110802118
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic pressures and life history predict trajectories of seagrass meadow extent at a global scale

Abstract: Seagrass meadows are threatened by multiple pressures, jeopardizing the many benefits they provide to humanity and biodiversity, including climate regulation and food provision through fisheries production. Conservation of seagrass requires identification of the main pressures contributing to loss and the regions most at risk of ongoing loss. Here, we model trajectories of seagrass change at the global scale and show they are related to multiple anthropogenic pressures but that trajectories vary widely with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 77 publications
1
51
0
1
Order By: Relevance
“…They provide ecosystem services including contributions to fisheries (Unsworth et al, 2019), carbon sequestration (Macreadie et al, 2014) and coastal protection (Koch et al, 2009). Seagrass meadows are threatened by multiple stressors such as ocean warming and poor water quality (Dunic et al, 2021; Thomson et al, 2015; Turschwell et al, 2021). The cumulative effects of such stressors will continue affecting seagrass habitats, as oceans continue to warm (Chefaoui et al, 2018) and land‐based activities degrade coastal ecosystems (Saunders et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…They provide ecosystem services including contributions to fisheries (Unsworth et al, 2019), carbon sequestration (Macreadie et al, 2014) and coastal protection (Koch et al, 2009). Seagrass meadows are threatened by multiple stressors such as ocean warming and poor water quality (Dunic et al, 2021; Thomson et al, 2015; Turschwell et al, 2021). The cumulative effects of such stressors will continue affecting seagrass habitats, as oceans continue to warm (Chefaoui et al, 2018) and land‐based activities degrade coastal ecosystems (Saunders et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Along the east coast of the USA, it is estimated that up to 50% of all eelgrass habitat has been lost in the past century, and the prospects for recovery in most of this area are low (Green and Short, 2003). More recently, a global assessment of seagrass trajectories found eelgrass extent to be in rapid decline in the region (Turschwell et al, 2021) where mean SST is warming at a rate of 0.4°C per decade (Alexander et al, 2018), and summer SST has increased more than 2°C since 1902 (Karmalkar and Horton, 2021). The large geographic coverage of our dataset and time-period in which it spans provide an opportunity to investigate the influence of changing temperature regimes on eelgrass in the Northeast USA.…”
Section: Introductionmentioning
confidence: 96%
“…At a global scale, significant meadow mortalities and subsequent loss of biodiversity related to seagrass die-offs have been correlated to MHWs occurrence (Marbà and Duarte, 2010;Fraser et al, 2014;Lefcheck et al, 2017;Nowicki et al, 2019;Shields et al, 2019;Smale et al, 2019;Strydom et al, 2020). The rates of seagrass decline, due to a wide variety of human activities (Duffy, 2006;Orth et al, 2006;Dunic et al, 2021;Turschwell et al, 2021), have accelerated from a median of 0.9% per year before the 1940's to 7% per year since 1990 (Waycott et al, 2009) and, even though encouraging results have been found for most of the fastgrowing species (de Los Santos et al, 2019), the alarming rate of deterioration might trigger significant ecological consequences. Warming in the Mediterranean Sea is two to three-fold faster than in the global ocean (Diffenbaugh et al, 2007) and a fast increase in the mean sea surface temperature (SST) and in the frequency and duration of MHWs is projected for the near future (Giorgi and Lionello, 2008).…”
Section: Introductionmentioning
confidence: 99%